Affective logic of competition images. Issue 3 (3rd July 2018) - Smitheram, Jan; Nakai Kidd, Akari; Meekings, Scott
Abstract : Architectural images operate through convention to depict, describe or identify a building as a means to communicate the content of a building. Competition images eschew this relationship slightly because they are staged images – images that act as a promise of a possible built future. Although there is a growing body of work looking at the interactions and transactions between different mediums, the architectural discipline is still focused on a critical reading of images. Our contribution is to give serious attention to the process of image production for architectural competitions, in particular the shift from a rationally driven logic of these images towards an amplification of affect. In this article we examine the affective logic of winning competition images by the architects Morphosis as well as Reiser and Umemoto's RUR Architecture P.C. to explore how these images are staged through composition, colour and cinematic expression. Based on these examples we argue critically that these images demonstrate a shift in image making in architecture which speaks of its intersection with media culture. Importantly, the images are also telling of a shifting expectation that architecture is not just a rational object or carrier of symbolic meaning but also a space that amplifies and stages experience.